Renal Involvement in Linear Nevus Sebaceous Syndrome—An Underrecognized Feature - Chonin Kuok; Kwaiyu Chan (Pediatric Reports, 2021)
Linear nevus sebaceous syndrome (LNSS) is a rare neurocutaneous disorder. It is characterized by the presence of nevus sebaceous, ocular anomalies, neurological deficits, and convulsion. Renal involvement was not commonly reported. We report a 10-year-old girl with LNSS who had concomitant cystic kidney disease and diffuse aortopathy with bilateral renal artery stenosis, leading to hypertension requiring oral anti-hypertensive medications. The girl presented with chorioretinal coloboma and multiple nevus sebaceous at birth. She had aortic coarctation and received surgical repair at one week of life. She had persistent hypertension during her follow-up. Further investigations were performed to look for causes of hypertension apart from possible re-coarctation. Her magnetic resonance angiogram revealed diffuse aortopathy, which extended from the aortic arch to the abdominal aorta. Branches of the aorta, including the celiac trunk, superior mesenteric arteries, and renal arteries, were also narrowed. Multiple renal cysts were also identified in her right kidney. Interventional angioplasty over the renal arteries was not feasible due to diffuse narrowing of the aorta, especially at the origins of renal arteries. The blood pressure was controlled with oral anti-hypertensive medications. Our case illustrated that pediatricians should be aware of the possible renal involvements in LNSS, which impose a significant impact on the management and long-term prognosis of these patients.